Determination of Ketamine, Fluoroketamine, Norketamine, and 2-Norfluoro-ketamine in Urine using Ultra-performance Liquid Chromatography-tandem Mass Spectrometry - Zhang, Meiling; Dong, Xicheng; Wang, Wanhang; Wang, Ziyue; Chen, Dizhong; Wen, Congcong; Wang, Xianqin (Current Pharmaceutical Analysis, 2024)
Objective: This study aimed to establish a simple, reliable, and sensitive method for detecting ketamine, fluoroketamine, and their metabolites in urine using UPLC-MS/MS. Methods: The chromatographic separation was performed on UPLC BEH C18 (50 mm × 2.1 mm, 1.7 μm) at a column temperature of 40°C. The mobile phase consisted of 0.1% formic acid aqueous solution and acetonitrile, with a flow rate set at 0.4 mL/min, following a specific elution procedure. A urine sample was treated with acetonitrile, and midazolam was used as an internal standard. Multiple reaction monitoring was used for quantitative analysis. Results: Ketamine, fluoroketamine, norketamine, and 2-norfluoro-ketamine exhibited linearity in urine (r>0.99) within the concentration range of 5-2000 ng/mL. Intra-day and inter-day precisions were 9% or less and 12% or less, respectively. The accuracy ranged from 92 to 107%. Mean recoveries were above 76%. The measured matrix effect was between 85 and 104%. Conclusion: This simple, reliable, and sensitive PLC-MS/MS method was successfully developed to determine ketamine, fluoroketamine, and their metabolite in rat urine.
Keywords: 2-norfluoro-ketamine